A Look Inside Mathematics Coaching: Roles, Content, and Dynamics - Mudzimiri, Rejoice; Burroughs, Elizabeth A.; Luebeck, Jennifer; Sutton, John; Yopp, David (Education Policy Analysis Archives, 2014)
Mathematics classroom coaching is used across the United States as a means for improving instruction, with the ultimate goal of improving student learning. The job assignments of coaches can vary widely across schools and districts.  Regardless of the various forms that coaching can take, there is the consistent expectation that a coach’s day-to-day work will positively influence classroom instruction. The study reported here attempts to gain a more complete picture of the job of an elementary mathematics coach based on the observation of seven coaches in five different districts for a day. We report the variety of ways we observed elementary mathematics coaches interact with teachers, and what roles and responsibilities they take on. Our analysis of these data led us to create a template for conducting observations of mathematics classroom coaching, which could be used by researchers seeking to conduct studies about coaching or by administrators seeking to document the day-to-day work of coaches.